Selected Decisions from the Amhara Supreme Court Cassation Bench - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2023)
These are two case reports from Reginal State of Amhara Supreme Court Cassation Division. The first one is about succession while the second one pertains to issues of homicide.